Outcomes of a Multicenter Safety and Efficacy Study of the SuitX Phoenix Powered Exoskeleton for Ambulation by Patients With Spinal Cord Injury - Koljonen, Paul Aarne; Virk, Anna Sternin; Jeong, Yoon; McKinley, Michael; Latorre, Juan; Caballero, Amaya; Hu, Yong; Wong, Yat Wa; Cheung, Kenneth; Kazerooni, Homayoon (Frontiers in Neurology, 2021)
Objective: To examine the safety and efficacy of ambulation utilizing a semi-passive and lightweight powered exoskeleton by spinal cord injury (SCI) patients. Methods: This is a multi-center, open-label, prospective cohort study across 3 facilities. A cohort of 40 individuals with SCI from T4-L5 was recruited into a 20-session training and assessment protocol, utilizing the SuitX Phoenix. All patients were tested using a 10-meter-walk test (10MWT), 6-minute-walk test (6MWT), and Timed up & Go test (TUG). Patient satisfaction, pain, exertion, changes in affect, as well as overall comfort and confidence were reported using a satisfaction survey, Rated Perceived Exertion (RPE) scale, and Positive and Negative Affect Schedule (PANAS). Safety outcomes, adverse events, and device malfunctions were reported. Results: 40 participants completed the study. There were no serious adverse events. All participants reported moderate to high levels of comfort and confidence using the device. All patients were able to achieve FIM of >4 on transitional movements and walking. The neurological level of injury had a statistically significant association in walking speed, WISCI, and FIM. Participants with an incomplete spinal cord injury had a higher FIM, faster speed, and higher WISCI in all outcome measures. Conclusion: This is the first study to examine the safety and efficacy of SuitX Phoenix for ambulation by SCI patients. We have shown that Phoenix is efficacious in allowing adults with SCI T4 to L5 perform walking and transitional movements. This study also reports the safety-profile of the device, user satisfaction, and psychological trends during training. (Abstract word count: 246)